2000
DOI: 10.1054/bjoc.2000.1226
|View full text |Cite
|
Sign up to set email alerts
|

Human anti-CD30 recombinant antibodies by guided phage antibody selection using cell panning

Abstract: SummaryIn various clinical studies, Hodgkin's patients have been treated with anti-CD30 immunotherapeutic agents and have shown promising responses. One of the problems that appeared from these studies is the development of an immune response against the nonhuman therapeutics, which limits repeated administration and reduces efficacy. We have set out to make a recombinant, human anti-CD30 single-chain variable fragment (scFv) antibody, which may serve as a targeting moiety with reduced immunogenicity and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…There are several reports mentioning similar lower affinity of human clones from guided selection compared to the murine counterpart (Klimka et al, 2000;Wang et al, 2000;Osbourn et al, 2005). Human anti-CD30 mAb which was isolated by guided selection showed 10-fold lower affinity compared to the mouse mAb (Klimka et al, 2000). The lower affinity and as a result lower efficacy of human clones from guided selection require the improvement of affinity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There are several reports mentioning similar lower affinity of human clones from guided selection compared to the murine counterpart (Klimka et al, 2000;Wang et al, 2000;Osbourn et al, 2005). Human anti-CD30 mAb which was isolated by guided selection showed 10-fold lower affinity compared to the mouse mAb (Klimka et al, 2000). The lower affinity and as a result lower efficacy of human clones from guided selection require the improvement of affinity.…”
Section: Discussionmentioning
confidence: 97%
“…Others reported the retention of epitope specificity between human scFv from guided selection and murine mAb which is already characterized the epitope and efficacy (Jespers et al, 1994;Klimka et al, 2000;Figini et al, 2009). And it is the advantage of guided selection that the epitope of well characterized murine mAb is retained in the human counterpart mAb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to other examples of human V L chain selection where the guided selection did not yield the most similar human counterpart sequence. 22,26,27,29,36 For the antigen binding site, more important than sequence homology are the canonical structures defined by Chothia et al 38,39 Previous studies have shown the isolation of human antibodies by guided selection, which shared these structural elements with the parental mouse antibody. In our case the three light chains did not share similar L1 and L3 canonical structures with the mouse antibody BSW17.…”
Section: Discussionmentioning
confidence: 99%
“…MG 7 antibody was confirmed to be of great value and good potency in the targeting gene therapy of gastric cancer due to the overexpression of its corresponding antigen in a large proportion of patients with gastric cancer. But owing to its murine origin, like many other similar antibodies, MG7 antibody can elicit human anti-mouse immunoreaction and thus its use in clinical practice is restricted [2,3] . One of the efficient solutions to this problem is to remove the constant region of antibody which makes main contribution to the immunogenicity of the murine antibody to human being.…”
Section: Introductionmentioning
confidence: 99%